2017
DOI: 10.1007/s12439-017-0232-6
|View full text |Cite
|
Sign up to set email alerts
|

Geriatrische Revalidatiezorg: De juiste dingen goed doen

Abstract: Nurses working in geriatric rehabilitation, experience apprehensiveness to perform their tasks adequately. Uncertainty about the client's reaction or fear of damaging the relationship of trust, results in nurses not involving the clients and informal care givers in the draw-up of the rehabilitation goals. Apprehensiveness also submerges as the lack of experience or specific competences in considering the client's other life events. The recommendations address these aspects in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…However, according to De Vos et al (2018), nurses experience a lack of confidence in performing their tasks in the multidisciplinary team. One can maybe attribute this to a knowledge gap when it comes to frailty in older people, the specific requirements of interdisciplinary teamwork and communication, to patients' expectations of nurses caring for them rather than being actively involved in rehabilitation and to an absence of clear working interventions (De Vos et al, 2018; Loft et al, 2017). As long as their share in the rehabilitation process remains unclear, the nurses' role in goal setting and achieving with older people will correspondingly remain undefined.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to De Vos et al (2018), nurses experience a lack of confidence in performing their tasks in the multidisciplinary team. One can maybe attribute this to a knowledge gap when it comes to frailty in older people, the specific requirements of interdisciplinary teamwork and communication, to patients' expectations of nurses caring for them rather than being actively involved in rehabilitation and to an absence of clear working interventions (De Vos et al, 2018; Loft et al, 2017). As long as their share in the rehabilitation process remains unclear, the nurses' role in goal setting and achieving with older people will correspondingly remain undefined.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the number of registered nurses working in geriatric rehabilitation has been seen (Inspectie Gezondheidszorg en Jeugd, 2022). One of the specific aspects that the nursing staff have been struggling with was voiced by De Vos et al (2018). DeVos et al found that nursing staff in geriatric rehabilitation in the Netherlands experience a certain apprehensiveness about performing goal-centered care in multidisciplinary teams.…”
Section: Introductionmentioning
confidence: 99%
“…DeVos et al found that nursing staff in geriatric rehabilitation in the Netherlands experience a certain apprehensiveness about performing goal-centered care in multidisciplinary teams. Clear working procedures might help the nursing staff in taking on their role (Cameron et al, 2018; De Vos et al, 2018; Loft et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the number of registered nurses working in geriatric rehabilitation has been seen (Inspectie Gezondheidszorg en Jeugd, 2022). One of the specific aspects that the nursing staff have been struggling with was voiced by De Vos et al (2018). DeVos et al found that nursing staff in geriatric rehabilitation in the Netherlands experience a certain apprehensiveness about performing goal-centered care in multidisciplinary teams.…”
Section: Introductionmentioning
confidence: 99%